Incidencia de la fertilización nitrogenada sobre la concentración de nutrientes en maíz - Goldman, V. (2002)
Corn (Zea mays L.) yields increased in the last years, and this increase has been associated with higher nutrient requirements. Nevertheless, nitrogen fertilization and the tillage system can produce changes in some soil characteristics and in the growth of crop roots that can improve the availability of other nutrients. The objectives of this work were to evaluate the effect of nitrogen fertilization and the tillage system on the concentration of macro and micronutrient in corn plants. Four experiments were conducted during the 1997/98 growing seasons. Three were conducted under conventional tillage (LC) in Balcarce, Paraná and Rafaela, and the other under LC and no-till (SD) in Balcarce. The treatments were N rate: 0, 70, 140 and 210 kg ha-1. Another treatment consisting of 140 kg N ha-1 plus sulfur, magnesium and zinc (140v) was also included. Macro and micronutrients were determined in leaf samples collected at flowering (opposite to- and below the ear). The results were interpreted according to critical values (NC) and sufficiency ranges (RSN). Nitrogen availability and tillage system affected significantly nitrogen accumulation, dry matter and grain yield. The higher nitrogen availability in Paraná and Rafaela generated luxury consumption of nitrogen, whereas in Balcarce low nitrogen availability caused high nitrogen use efficiency. The addition of nitrogen increased sulfur and manganese leaf concentration in all experiments but did not affect calcium and magnesium concentrations. In Balcarce, this treatment also increased phosphorus, potassium, iron, copper and zinc concentration. The application of magnesium, sulfur and zinc at sowing did not improve corn yield. Under SD there were lower leaf nitrogen, potassium and iron concentration at flowering. The RSN at flowering, indicated that potassium, magnesium, sulfur, copper and zinc were the most limiting nutrients. However, grain yields were close to the potential yield for this locations.